Matthew and the Pauline Corpus: A Preliminary Intertextual Study* - Sim, David C. (Journal for the study of the New Testament, 2009)
This study investigates the possibility that the author of Matthew's Gospel had access to the letters of Paul. Using the methods of intertextuality, it establishes criteria for determining whether this was indeed the case and concludes that it is more probable than not that the evangelist did know the Pauline epistles. An intertextual relationship between the Gospel and the Pauline corpus becomes clear once we understand that Matthew, as a Law-observant Christian Jew, was opposed to the more liberal theology of Paul. A single test case reveals that the evangelist was reacting to certain claims of the apostle expressed in his letters, and raises the prospect of further intertextual connections between these early Christian documents.